The man in the iron mask - Dumas, Alexandre, 1802-1870.; Neugroschel, Joachim (New York : Penguin Books, 2003)
When the destinies of King Louis XIV and a mysterious prisoner in an iron mask converge, the Three Musketeers and D'Artagnan find themselves caught between conflicting loyalties.
Includes bibliographical references (p. xxiv-xxv).
Keywords: Man in the Iron Mask -- Fiction; France -- History -- Louis XIV, 1643-1715 -- Fiction